Gradient ion chromatographic determination of rare earth elements in coal and fly ash - Ridley, Mark K (Department of Geological Sciences, 2016)
Rare Earth Element (REE) determination in samples of coal and fly ash was undertaken by gradient high performance ion chromatography (HPIC). Ion chromatographic analysis requires that samples be in solution and that the matrix transition metals be removed. Coal samples, weighing 0.20g, were successfully dissolved in sealed pressure vessels in a microwave oven. Standard ashing procedures, followed by acid dissolution, were carried out to allow comparison with the microwave digestion technique. A lithium metaborate/tetraborate fusion and acid dissolution technique was used for the dissolution of fly ash. For the technique of REE determination the sample matrix was removed by off-line cation exchange. In an initial stage of the HPIC analysis the transition metals were removed by anion exchange using pyridine-2,6 dicarboxylic acid. The REE were then analysed using gradient elution of oxalic and diglycolic acid. Typically a 100μ1 volume of sample solution was employed for REE determination, but in the case of low ash (low REE) coal samples, prepared by microwave digestion, on-line concentration of 3-5 ml of sample, was necessary. The separated REE were reacted with 4-(2-pyridylazo)-resorcinol (PAR) and detected photometrically using a visible light detector at a wavelength of 520nm. Reproducibility for each REE was typically better than 5%CoV. Results from the analysis of coal and fly ash international standard reference materials were in acceptable agreement with values from alternative analytical procedures. Smooth, coherent trends obtained when the data were plotted on chondrite and "shale composite" normalised diagrams provided some support for the accuracy of the technique. The application of HPIC to the determination of REE in coals was demonstrated by the analysis of a new international reference coal sample, USGS CLB-1. Differences in REE concentrations between coal samples prepared by microwave digestion and ashing were observed. The HPIC analytical technique was also applied to the determination of REE in fly ash. The REE concentrations of fly ash from sequential electrostatic precipitators, from Lethabo and Kendal power stations, were determined to elucidate the behaviour of REE after the combustion of coal. REE concentrations increased through the sequential precipitators.